2016
DOI: 10.1007/s11906-016-0629-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor Stabilizers: a New Avenue for Reducing BP While Helping Hemoglobin?

Abstract: Anemia of chronic kidney disease (CKD) is common and is associated with diminished quality of life, cognitive impairment, cardiovascular morbidity, hospitalizations, and mortality. As the prevalence of end-stage renal disease continues to rise, the management of anemia represents a growing economic burden. Erythropoiesis-stimulating agents (ESA) are the mainstay of anemia management but their use is limited due to the associated cardiovascular adverse events. Prolyl hydroxylase domain enzyme (PHD) inhibitors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 181 publications
0
21
0
Order By: Relevance
“…Potential upregulation of the vascular endothelial growth factor (VEGF) gene as a result of HIF stabilization could adversely impact tumor growth and accelerate proliferative retinopathy in diabetics. Phase II studies in vadadustat and daprodustat have not demonstrated any significant change in VEGF, and in a VEGF-sensitive model of spontaneous breast cancer, roxadustat was not associated with tumor initiation, progression, or metastases [68,72].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Potential upregulation of the vascular endothelial growth factor (VEGF) gene as a result of HIF stabilization could adversely impact tumor growth and accelerate proliferative retinopathy in diabetics. Phase II studies in vadadustat and daprodustat have not demonstrated any significant change in VEGF, and in a VEGF-sensitive model of spontaneous breast cancer, roxadustat was not associated with tumor initiation, progression, or metastases [68,72].…”
Section: Discussionmentioning
confidence: 97%
“…With the former, both daprodustat and roxadustat, but not vadadustat, have been shown to reduce lipids, with no published data on molidustat. There is very limited evidence to support any role in reducing blood pressure, although this will be explored in phase III trials [68]. The pleiotropic effects of the HIF pathway, however, do raise some potential concerns regarding safety, which will be addressed in the phase III trials.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have been applied to the treatment of renal anaemia in which there is a deficiency of erythropoietin [22,23]. The administration of these compounds is associated with an improved iron profile and an increase of endogenous erythropoietin production to near the physiological range.…”
Section: Consequences Of Hypoxiamentioning
confidence: 99%
“…The clinical trials currently underway aim to address whether PHD enzyme inhibitors will improve clinical end-points, including cardiovascular events [24]. PHD inhibitors have been reported to reduce blood pressure [22] and plasma cholesterol concentrations [19]. Hence, there is a good reason to believe that some PHD inhibitors will reduce cardiovascular endpoints in patients with renal disease.…”
Section: Consequences Of Hypoxiamentioning
confidence: 99%
“…Accruing evidence has suggested that the balance between HIF-1α and HIF-2α is of crucial importance for the maintenance of systemic arterial pressure [41] . Transcription of HIF-1α leads to an increased expression of NO synthase 2 and consequently increased NO production whereas transcription of HIF-2α indirectly reduces NO production [42,43] .…”
Section: Concerns With Hif Stabilizersmentioning
confidence: 99%